Methods for detention of lipid rancidity - Nagy, Mária; Győri, Zoltán; Borbélyné Varga, Mária (Acta Agraria Debreceniensis, 2020)
There are various methods available for measurement of lipid oxidation in foods.Changes in chemical, physical, or organoleptic properties of fats and oils during oxidation may be monitored to assess the extent of lipid oxidation. However, there is no uniform and standard method for detecting all oxidative changes in all food systems. The available methods to monitor lipid oxidation in foods and biological systems may be divided into two groups. The first group measures primary oxidative changes and the second determines secondary changes that occur in each system.